2018
DOI: 10.1016/j.molcel.2017.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Removal of RTF2 from Stalled Replisomes Promotes Maintenance of Genome Integrity

Abstract: The protection and efficient restart of stalled replication forks is critical for the maintenance of genome integrity. Here, we identify a regulatory pathway that promotes stalled forks recovery from replication stress. We show that the mammalian replisome component C20orf43/RTF2 (homologous to S. pombe Rtf2) must be removed for fork restart to be optimal. We further show that the proteasomal shuttle proteins DDI1 and DDI2 are required for RTF2 removal from stalled forks. Persistence of RTF2 at stalled forks r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 63 publications
(78 reference statements)
1
73
1
Order By: Relevance
“…Many publications describing yeast Ddi1 have focused on its role as a proteasomal shuttling protein, bringing polyubiquitinated substrates to the 26S proteasome (Clarke et al 2001;Finley 2009;Ivantsiv et al 2006;Kaplun et al 2005;Voloshin et al 2012). A shuttling mechanism has also been proposed for human Ddi1-like proteins in the degradation of RTF2 and subsequent restart of replication forks (Kottemann et al 2018). In contrast, our data do not support the proteasome shuttling mechanism, as deletion of UBL, UBA or both did not impair the ability of the protein to rescue hydroxyurea sensitivity.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Many publications describing yeast Ddi1 have focused on its role as a proteasomal shuttling protein, bringing polyubiquitinated substrates to the 26S proteasome (Clarke et al 2001;Finley 2009;Ivantsiv et al 2006;Kaplun et al 2005;Voloshin et al 2012). A shuttling mechanism has also been proposed for human Ddi1-like proteins in the degradation of RTF2 and subsequent restart of replication forks (Kottemann et al 2018). In contrast, our data do not support the proteasome shuttling mechanism, as deletion of UBL, UBA or both did not impair the ability of the protein to rescue hydroxyurea sensitivity.…”
Section: Discussioncontrasting
confidence: 93%
“…As part of a genome-wide synthetic lethality screen in yeast, Ddi1 exhibited a strong negative genetic interaction with Wss1, another replication stress-countering protease (Costanzo et al 2016). Another study identified human proteins DDI1 and DDI2, mammalian orthologues of Ddi1 that are involved in degradation of the replication termination factor RTF2, facilitating restart of stalled replication forks (Kottemann et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RMSD values of the flap of one subunit (subunit A) increased over the course of the simulation and stabilized at about 4. 5 A, whereas that of the flap of the other subunit (subunit B) showed a similar increase during the initial duration but eventually decreased and stabilized at about 3 A near the end of the 300 ns run (Fig. 6A).…”
Section: Simulationmentioning
confidence: 76%
“…But when one subunit of each Ddi1-RVP dimer is superimposed, the second subunits deviate in position with RMSD values of 1.0-1. 5 A due to slightly differing angles (2.3-5.4°) between the two subunits in each dimer, suggesting a small relative movement of the subunits (Fig. 9).…”
Section: Docking Studies With Hiv-1 Pr Inhibitorsmentioning
confidence: 99%